A backward glance. Arriving at the punched-card system. (IEEE spectrum)
Herman Hollerith's punched-card machine for the US Census office consisted of: a bank of counters for tabulating results; a hand-operated reader that pushed wire contacts through the holes in the card into pools of mercury, completing an electrical circuit; and a sorting box with bins for holding the cards after they were read. An historical overview of this technology is presented by the author in this paper